Soil applied boron combined with boron-tolerant bacteria (Bacillus Sp. MN54) improve root proliferation and nodulation, yield and agronomic grain biofortification of chickpea (Cicer arietinum L. ) - Mehboob, Noman; Hussain, Mubshar; Minhas, Waqas Ahmed; Yasir, Tauqeer Ahmad; Muhammad Naveed; Farooq, Shahid; Alfarraj, Saleh; Tan, Ali Kee Zuan (MDPI AG, 2021)
Chickpea is widely cultivated on calcareous sandy soils in arid and semi-arid regions of Pakistan; however, widespread boron (B) deficiencies in these soils significantly decreases its productivity. Soil application of B could improve chickpea yield and grain-B concentration. However, optimizing suitable B level is necessary due to a narrow deficiency and toxicity range of B. Nonetheless, the co-application of B-tolerant bacteria (BTB) and synthetic B fertilizer could be helpful in obtaining higher chickpea yields and grain-B concentration. Therefore, this study optimized the level of soil applied B along with BTB, (i.e., Bacillus sp. MN54) to improve growth, yield and grain-B concentrations of chickpea. The B concentrations included in the study were 0.00 (control), 0.25, 0.50, 0.75 and 1.00 mg B kg−1 soil combined with or without Bacillus sp. MN54 inoculation. Soil application of B significantly improved root system, nodulation, yield and grain-B concentration, and Bacillus sp. MN54 inoculation further improved these traits. Moreover, B application at a lower dose (0.25 mg B kg−1 soil) with BTB inoculation recorded the highest improvements in root system (longer roots with more roots’ proliferation), growth, nodulation and grain yield. However, the highest grain-B concentration was recorded under a higher B level (0.75 mg B kg−1 soil) included in the study. Soil application of 0.25 mg B kg−1 with Bacillus sp. MN54 inoculation improved growth and yield-related traits, especially nodule population (81%), number of pods plant−1 (38%), number of grains plant−1 (65%) and grain yield (47%) compared with control treatment. However, the grain-B concentration was higher under the highest B level (1.00 mg kg−1 soil) with Bacillus sp. MN54 inoculation. In conclusion, soil application of 0.25 mg B kg−1 with Bacillus sp. MN54 inoculation is a pragmatic option to improve the root system, nodule population, seedling growth, yield and agronomic grain-B biofortification of chickpea.